Daya Tarik Keanekaragaman Burung di Jalur Hijau Jalan Kota Yogyakarta - Retno Nur Utami; Siti Nurul Rofiqo Irwan; Ahmad Sawardi; Alia Bihrajihant Raya (Institut Pertanian Bogor, 2021)
Urban greenery plays an important role in providing a biodiversity habitat of vegetation and birds as biotics in the urban ecosystem. The biodiversity can show attractions in Yogyakarta city as a tourism destination in Indonesia. This research was conducted on three types of roads of the secondary artery (SA), secondary collector (SC), and local (L). The bird diversity depended on tree greenery as its habitat and food source. This research aimed (1) to analyze bird diversity on the roadside greenery in Yogyakarta City, and (1) to reveal the attraction of birds on the urban greenery as a tourism attraction. The sample units were selected by the method of stratified random sampling. The bird observation was used by the method of transect line conducted on the three categories of roads in Yogyakarta City. The bird diversity was analyzed by Shannon-Wiener's (H') index diversity, and bird activity was descriptively analyzed. The number of birds found in the greenery was 685 belong to 12 species. The diversity indexes (H') of the birds on the roads of the secondary artery (SA), secondary collector (SC), and local (L) categories were 0.697 (low), 1.001 (medium), and 1.246 (medium). The index shows the equal quality of the bird attractions in the city. The low-medium of index value should be improved to reach a high H'. The improvement should be carried out by landscape planning for urban tourism through planting food source trees or habitat trees for birds on the urban greenery of Yogyakarta. The strength of the urban attraction of birds was also supported by species diversity, conservation status, bird activity, habitat trees, and the ecological function of urban trees on the roadside greenery of Yogyakarta city. Keywords: bird diversity, roadside greenery, urban attraction, urban greenery, Yogyakarta